Temporal stability of spatial cytotype structure in mixed-ploidy populations of Centaurea stoebe - Mráz, Patrik; Španiel, Stanislav; Skokanová, Katarína; Šingliarová, Barbora (AoB PLANTS, 2022)
Spatial segregation of cytotypes reduces the negative effect of frequency-dependent mating on the fitness of minority cytotype(s) and thus allows its establishment and coexistence with the majority cytotype in mixed-ploidy populations. Despite its evolutionary importance, the stability of spatial segregation is largely unknown. Furthermore, closely related sympatric cytotypes that differ in their life histories might exhibit contrasting spatial dynamics over time. We studied the temporal stability of spatial structure at a secondary contact zone of co-occurring monocarpic diploids and polycarpic tetraploids of Centaurea stoebe, whose tetraploid cytotype has undergone a rapid range expansion in Europe and became invasive in North America. Eleven years after the initial screening, we re-assessed the microspatial distribution of diploids and tetraploids and their affinities to varying vegetation-cover density in three mixed-ploidy populations in Central Europe. We found that overall, spatial patterns and frequencies of both cytotypes in all sites were very similar over time, with one exception. At one site, in one previously purely 2x patch, diploids completely disappeared due to intensive succession by shrubby vegetation. The remaining spatial patterns, however, showed the same cytotype clumping and higher frequency of 2x despite subtle changes in vegetation-cover densities. In contrast to the expected expansion of polycarpic tetraploids having higher colonization ability when compared to diploids, the tetraploids remained confined to their former microsites and showed no spatial expansion. Spatial patterns of coexisting diploids and tetraploids, which exhibit contrasting life histories, did not change over more than a decade. Such temporal stability is likely caused by relatively stable habitat conditions and very limited seed dispersal. Our results thus imply that in the absence of a disturbance regime connected with frequent human- or animal-mediated seed dispersal, spatial patterns may be very stable over time, thus contributing to the long-term coexistence of cytotypes.
Keywords: invasion; polycarpy; flow cytometry; mixed-ploidy population; disturbance; Centaurea stoebe; polyploidy; spatial cytotype structure; cytotype coexistence; colonization; spatial segregation; secondary contact zone